Complex Interdependence Between Indonesia-Australia Through Cybersecurity Cooperation Post-Indonesia-Australia Cyberwar in 2013 - Elva Azzahra Puji Lestari (Jurnal Hubungan Internasional, 2021)
The geographical proximity between Indonesia and Australia leads to harmonious relations between these two countries, especially in security. The development of information technology is one of the areas becoming the focus of Indonesia and Australia in maintaining regional security. Security cooperation has been established between Indonesia and Australia. This development can have an impact on a dispute between Indonesia and Australia, particularly in the 2013 cyberwar conflict. An Australian cyber-attack on Indonesia by tapping President Yudhoyono’s communication network caused the cyberwar incident. However, the post-cyberwar between Indonesia and Australia did not cause tension in the relations between the two countries. Indonesia approved the MOU of Cybersecurity Cooperation with Australia in 2018. This study aims to analyze the causes of Indonesia and Australia’s choice to continue their cybersecurity cooperation after the Indonesia-Australia cyberwar in 2013. This research utilized the theory of complex interdependence and domestic politics and qualitative analysis methods. The results revealed that Australia’s soft power resources, Australia’s political credibility, the advantages of Indonesia and Australia as democratic countries, and the political survival of individual leaders caused both countries to continue their cybersecurity cooperation after the Indonesia-Australia cyberwar in 2013.